Role of Antimicrobial Susceptibility Testing before First-Line Treatment Containing Clarithromycin for Helicobacter pylori Eradication in the Clinical Setting - Seokin Kang; Yuri Kim; Ji Yong Ahn; Hwoon-Yong Jung; Nayoung Kim; Hee Kyong Na; Jeong Hoon Lee; Kee Wook Jung; Do Hoon Kim; Kee Don Choi; Ho June Song; Gin Hyug Lee (MDPI AG, 2021)
Background: Checking Helicobacter pylori susceptibility tests in the clinical setting before first-line treatment is considered difficult. We compared susceptibility-guided therapy (SGT) with empirical therapy (ET) as a first-line treatment containing clarithromycin and investigated the eradication rate using antimicrobial susceptibility testing (AST). Methods: 257 patients with H. pylori infection, with AST, performed before the eradication of clarithromycin-containing regimens were enrolled and divided into two groups: the SGT and ET groups. Results: Eradication rates in the SGT and ET groups were 85.4% and 58.4% (P < 0.01), respectively. In triple therapy (TT), eradication rates of the SGT and ET groups were 85.1% and 56.6% (P < 0.01), respectively. In sequential therapy (SET), eradication rates of the SGT and ET groups were 86.2% and 65.6% (P = 0.06), respectively. According to AST, TT had an eradication rate of 84.6% with strains susceptible to clarithromycin and amoxicillin and 11.1% with strains resistant to both. SET had an eradication rate of 89.5% with strains susceptible to clarithromycin, amoxicillin, and metronidazole, whereas it was 0% with strains resistant to clarithromycin and metronidazole. Conclusions: SGT as first-line treatment improved eradication rates of TT and SET by 28.5 (P < 0.01) and 20.6 (P = 0.06) percent points, respectively, compared with ET.